Traffic noise prediction in bandar mahkota cheras using calculation of road traffic noise (CORTN) - Gan, Yuyun (2023)
Noise pollution is a worldwide issue that grows tremendously, especially in the cities areas due to urbanization. Nowadays, the major source of environmental noise is transportation noise, or known as traffic noise. The increasing population lead to an increase in the number of transportation and subsequently contributes to a higher level of road traffic noise. Research on traffic noise is needed to ensure the noise levels are within the acceptable range by referring to the road traffic noise regulations. Studies proved that the CoRTN model was able to provide accurate estimation in Macau, Nigeria and Malaysia. Hence, this study has been conducted, which aimed to investigate the performance of the CoRTN noise prediction model in estimating the road traffic noise level of a road in Bandar Mahkota Cheras. This study has been carried out with the objectives to measure the traffic noise level in Bandar Mahkota Cheras, as well as to develop a noise prediction model, referring to the CoRTN model, using MATLAB. The reliability and accuracy of the CoRTN model were then validated by comparing the measured and predicted noise levels. Field measurements with four control points for peak hour and off-peak hour at Jalan Permaisuri in Bandar Mahkota Cheras were conducted in this study. A noise prediction model has been developed using MATLAB and proven to be workable since the predicted noise level obtained was similar to the value provided in CoRTN for a type of road condition. Besides, by comparing the predicted noise level with the data collected, the results obtained for